Simple mathematical model of sacroiliac screws safe‐zone—Easy to implement by pelvic inlet and outlet views. Issue 7 (19th September 2016) - Herman, Amir; Keener, Emily; Dubose, Candice; Lowe, Jason A.
ABSTRACT: Percutaneous sacral screw fixation is the mainstay of posterior pelvic ring fixation. This study quantifies the accuracy of fluoroscopic screw placement using post‐operative CT scans and redefines the fluoroscopic safe zone using a mathematical calculation obtained from Inlet and outlet images. The authors hypothesized that a mathematical calculation of screw placement within the ala will improve accuracy of screw placement. A retrospective review of consecutive patients admitted to a level 1 trauma center with pelvic fractures fixed with iliosacral screws from January 2011 to December 2014 was performed. Accuracy of screw placement was determined by comparing fluoroscopy to post‐operative CT scans. A mathematical calculation of screw position within the sacral ala was applied to determine assess screw position and compared to CT findings. Ninety‐four patients with 156 screws met inclusion criteria, of which 50 (32.0%) had a cortical breech on CT. The sensitivity and specificity of the inlet–outlet safe zone using mathematical calculation were 97.1% and 84.0%, respectively. The positive and negative predictive values were 92.7% and 93.3%, respectively. Overall accuracies of the radiographic inlet–outlet and lateral safe zones were 92.9% and 70.0%, respectively ( p ‐value = 0.004). Sacral dysmorphism was not found to be associated with sacral cortical breech. A Simple mathematical calculation (screw position relative to percentage of bone width) on the inlet–outlet provides an accurate way to predict the accuracy of sacroiliac screws. The method is easy to implement, part of the surgery work‐flow, and provides higher accuracy than relying on subjective interpretation of inlet, outlet, and lateral images. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1478–1484, 2017.